2019
DOI: 10.3390/molecules24091721
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aluminum Content in Certain Brain Structures is Correlated with Higher Silicon Concentration in Alcoholic Use Disorder

Abstract: Introduction: Alcohol overuse may be related to increased aluminum (Al) exposure, the brain accumulation of which contributes to dementia. However, some reports indicate that silicon (Si) may have a protective role over Al-induced toxicity. Still, no study has ever explored the brain content of Al and Si in alcoholic use disorder (AUD). Materials and methods: To fill this gap, the present study employed inductively coupled plasma optical emission spectrometry to investigate levels of Al and Si in 10 brain regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…Among heavy drinkers, alcoholic liver disease is estimated to develop in 15–30% [ 2 ]. In patients who consume excessive amounts of alcohol, various types of disturbances are observed, i.e., electrolyte, acid-base, protein-caloric malnutrition, and vitamin deficiency [ 3 , 4 , 5 ]. Chronic alcohol abuse patients are malnourished not only because of a diet low in nutrients but also because alcohol impairs the absorption of essential nutrients and elements.…”
Section: Introductionmentioning
confidence: 99%
“…Among heavy drinkers, alcoholic liver disease is estimated to develop in 15–30% [ 2 ]. In patients who consume excessive amounts of alcohol, various types of disturbances are observed, i.e., electrolyte, acid-base, protein-caloric malnutrition, and vitamin deficiency [ 3 , 4 , 5 ]. Chronic alcohol abuse patients are malnourished not only because of a diet low in nutrients but also because alcohol impairs the absorption of essential nutrients and elements.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more cases of the proximal GC than the distal one are observed among patients [8]. Numerous risk factors contribute to the onset of GC, among which Helicobacter pylori (H. pylori) infection, genetic factors, imbalanced diet, as well as excessive alcohol consumption, are of the highest importance [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Wykazano, że u osób z BPD występują polimorfizmy genu FKBP5 kodującego białko biorące udział w regulacji receptorów glukokortykosteroidowych, co wpływa na dysfunkcję osi HPA [14,15]. BPD często współwystępuje z chorobą alkoholową, przy czym nadmierne spożywanie alkoholu indukuje znaczne zmiany w obrębie centralnego oraz obwodowego układu nerwowego [16][17][18][19]. Wśród czynników środowiskowych mających znaczenie w patogenezie zaburzenia borderline wymienia się fizyczną przemoc dziecięcą, nadużycia seksualne, czy zaniedbanie w dzieciństwie [20][21][22][23].…”
Section: Wstępunclassified
“…It was shown that in patients with BPD, the polymorphism of the FKBP5 gene is quite common; this gene encodes the protein that is involved in the processes that regulate glucocorticoid receptors, which ultimately has an impact on the HPA dysfunctions [14,15]. BPD usually coexists with alcohol use disorder and an excessive alcohol intake additionally induces changes within the central and peripheral nervous systems [16][17][18][19]. Among environmental factors that are crucial in the pathogenesis of BPD, physical abuse of children, sexual abuse, or negligence in childhood are usually mentioned [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%